Influence of ESGC Indicators on Financial Performance of Listed Pharmaceutical Companies. - López-Toro, Alberto A.; Sánchez-Teba, Eva María; Benítez-Márquez, María Dolores; Rodríguez-Fernández, Mercedes (MPDI, 2021)
The pharmaceutical industry, concerned about the impact of its activity, has integrated responsible principles and practices with a view to improving its sustainable and financial performance. This study analyzes the relationship between environmental, social, governance, and controversy indicators and financial performance, measured through return on equity (ROA), return on assets (ROE), and Tobin’s Q, which are applied to the listed companies in the Nasdaq US Smart Pharmaceuticals Index. This index is composed of 30 international companies with a presence at the global level. All the data have been extracted from the Thomson Reuters database. The analysis was performed using structural equation modeling implemented with partial least squares. The results confirm the positive relationship between the construct composed of environmental, social, and governance (ESG) indicators and the aforementioned financial ratios. Additionally, a positive relationship of the controversy indicator with Tobin’s Q is supported. This suggests that the pharmaceutical multinationals focus their investments in sustainability on ESG and pay attention to controversies to boost the visibility of the company and thus increase its value. These conclusions confirm that investing in ESG is a profitable strategy. It is also relevant for managers as it increases the profits and the market value of multinational pharmaceutical companies.
Keywords: Industria farmacéutica; Responsabilidad social de la empresa; Análisis multivariante; Análisis financiero; ESGC indicators; Controversies; Financial performance; Pharmaceutical industry; Stakeholder theory; PLS-SEM